Analyzing company performance using the Balanced Scorecard method: A case study in an automotive spare parts manufacturing company - Arifin, Mohammad Mawan; Agustin, Meilan; Fawwazi, Muhammad Farrel (Universitas Sultan Ageng Tirtayasa, 2023)
Business competition in today's corporate landscape is fiercely competitive, demanding sustainable strategies for growth and success. This research endeavors to evaluate the performance of Nutech Pundi Arta, a spare parts manufacturer company, and offer recommendations derived from performance assessments to facilitate the company's advancement. The balanced scorecard serves as the comprehensive measurement framework, structured across four perspectives: financial, customer, internal business processes, and learning and growth. Data collection involved interviews, documentation review, and questionnaires administered to leaders, employees, and customers of Nutech Pundi Arta. The evaluation of Nutech Pundi Arta's performance, based on the Balanced Scorecard method from 2018 to 2020, reveals several noteworthy insights. When considering its business strategy, the company performs admirably, emphasizing the strategic objective attribute as the strongest. However, from a financial standpoint, the Net Profit Margin (NPM) ratio exhibits inefficiency, reflected in a decrease in NPM from 2019 to 2020, owing to escalated interest costs and a disproportionate rise in sales to profits. Conversely, the customer perspective reflects a highly favorable image, indicating positive customer sentiments toward the company. Evaluation from the internal business processes perspective yields a positive performance rating, while the learning and growth perspective highlights exceptional performance. To enhance Nutech Pundi Arta's overall performance, particularly in the financial domain, it is recommended to address the high interest costs and align sales growth with profit increment. Additionally, to ensure long-term development, a customer-centric approach along with continued emphasis on internal processes and learning and growth strategies is advised, affirming the company's commitment to prioritizing its strategic goals.